Tecnología educativa en tiempos de pandemia COVID-19 y su aporte en el desarrollo del aprendizaje de los estudiantes de 3ro Bachillerato Contabilidad en la Unidad Educativa Emigdio Esparza Moreno - Periodo lectivo 2021 -2022 - Toalombo Parraga, Carlos Elian (2022)
The present case study called, "Educational technology in times of the covid-19 pandemic and its contribution in the development of learning of accounting 3rd baccalaureate students in the "Emigdio Esparza Moreno" educational unit - class period 2021 -2022", is I do it with the purpose of being able to find the valuable contribution that technologies provide in current education and much more because it is an engine that helped in the coronavirus pandemic, this work was carried out through a quantitative study methodology that through the use of a data collection technique such as the survey, I show the enormous importance of information systems and their enormous set of tools in education, such as virtual platforms, and the use of digital tools for the development of tasks that are executed by the decent ones of the respective unit.